The investment performance of ethical equity funds in Malaysia - Fadillah Mansor; Muhammad Ishaq Bhatti; Shafiqur Rahman; Do Hung Quang (Journal of Risk and Financial Management, 2020)
This paper investigates the investment performance of Malaysian Islamic equity funds and a matching sample of conventional equity funds relative to their market benchmark. An integrated model is used to simultaneously capture the market timing and selectivity skills of fund managers. Our findings indicate that the Islamic funds do not match the performance of the conventional funds in terms of selectivity skill. However, Islamic funds perform no worse than their conventional counterparts in market timing, although neither outperform the market. These findings have crucial implications not only for fund managers' investment decisions, but also for sensitive shariah-compliant investors and risk-seeking investors of Islamic equity funds in their investment portfolio preference.
Keywords: 330; investment performance; Islamic equity funds; Islamic finance; market timing; portfolio investment; selectivity skill